Chemotherapy and Targeted Therapy for Patients With Human Epidermal Growth Factor Receptor 2–Negative Metastatic Breast Cancer That is Either Endocrine-Pretreated or Hormone Receptor–Negative: ASCO Guideline Update. Issue 35 (10th December 2021) - Moy, Beverly; Rumble, R. Bryan; Come, Steven E.; Davidson, Nancy E.; Di Leo, Angelo; Gralow, Julie R.; Hortobagyi, Gabriel N.; Yee, Douglas; Smith, Ian E.; Chavez-MacGregor, Mariana; Nanda, Rita; McArthur, Heather L.; et al.
Abstract : PURPOSE: This guideline updates recommendations of the ASCO guideline on chemotherapy and targeted therapy for patients with human epidermal growth factor receptor 2–negative metastatic breast cancer (MBC) that is either endocrine-pretreated or hormone receptor (HR)–negative. METHODS: An Expert Panel conducted a targeted systematic literature review guided by a signals approach to identify new, potentially practice-changing data that might translate into revised guideline recommendations. RESULTS: The Expert Panel reviewed abstracts from the literature review and retained 14 articles. RECOMMENDATIONS: Patients with triple-negative, programmed cell death ligand-1–positive MBC may be offered the addition of immune checkpoint inhibitor to chemotherapy as first-line therapy. Patients with triple-negative, programmed cell death ligand-1–negative MBC should be offered single-agent chemotherapy rather than combination chemotherapy as first-line treatment, although combination regimens may be offered for life-threatening disease. Patients with triple-negative MBC who have received at least two prior therapies for MBC should be offered treatment with sacituzumab govitecan. Patients with triple-negative MBC with germline BRCA mutations previously treated with chemotherapy may be offered a poly (ADP-ribose) polymerase inhibitor rather than chemotherapy. Patients with HR-positive human epidermal growth factor receptor 2–negative MBC for whom chemotherapy is being considered should be offered single–agent chemotherapy rather than combination chemotherapy, although combination regimens may be offered for highly symptomatic or life-threatening disease. Patients with HR-positive MBC with disease progression on an endocrine agent may be offered treatment with either endocrine therapy with or without targeted therapy or single-agent chemotherapy. Patients with HR-positive MBC with germline BRCA mutations no longer benefiting from endocrine therapy may be offered a poly (ADP-ribose) polymerase inhibitor rather than chemotherapy. No recommendation regarding when a patient's care should be transitioned to hospice or best supportive care alone is possible. Additional information is available at www.asco.org/breast-cancer-guidelines .